Cognitive Experience in Positivism and Pragmatism - Lyubiviy, Y. V.; Samchuk, R. V. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The main purpose of the article is to compare the anthropological context of the concept of cognitive experience in pragmatism, which is based on an empirical basis and is determined by the result of the interaction of a person as a biosocial being with the surrounding natural and social environment through experimentation and choosing the most optimal way of acting in a given situation in accordance with individual and social values, on the one hand, and the exclusively epistemological significance of cognitive experience in positivism, aimed at observation and verification empirical data, on the other hand. Theoretical basis. The anthropological approach is important for this study, since its defining theoretical idea is the focus on the inseparability of theoretical and practical approaches to the integrity of human activity, proposed by pragmatism. Unlike positivism, which absolutizes theoretical knowledge of reality, supported by empirical experience, pragmatism understands this knowledge as an element of the practical adaptive activity of a person as a biosocial being who constructs the natural and social environment necessary for his/her life, transforming uncertainty into certainty. Thus, from the position of radical empiricism of W. James, a person’s cognitive experience includes not only knowledge of what is before a person’s eyes "here and now", but also values, interests, moral feelings that determine the purpose, prospects and motives of his/her activity. Originality. Thanks to an anthropological approach, pragmatism achieves a more complete understanding of cognitive experience than positivism. If in positivism cognitive experience is valuable in itself, then in pragmatism it, through feedback, performs the function of reflective practical experimentation, which should ensure the effectiveness of practical actions of a person as a biosocial being. Cognitive experience is an important component of habit, which for pragmatism is, on the one hand, the accumulated experience of a person’s long-term practical adaptation to the natural and social environment, and on the other – a person’s ability to find innovative ways of survival in the event of a change in the determining circumstances of life support. Thus, in extreme existential conditions of human existence (ecological and social disasters, wars), human-centred and socio-centred values, including identity values, together with strategically verified pragmatic optimality of actions, provided by cognitive experience, are important for the survival and development of man and society. Conclusions. Using an anthropological approach, pragmatism considers cognitive experience in a human-dimensional aspect. From the entire spectrum of cognitive experience, which enables a person to navigate in the natural and social environment, there is a part that allows a person to apply the acquired knowledge in productive practical activities based on universal values. From the point of view of pragmatism, cognitive experience based on experimentation with reflective feedback is important for ensuring the effectiveness of human practical actions. In the conditions of epoch-making social transformations currently taking place in the world, the survival and development of a civilization based on universal human values largely depends on the effectiveness of the actualized cognitive experience of a person, his or her intellectual and moral resources.